MetNC: Predicting Metabolites in vivo for Natural Compounds - Chen, Zikun; Yan, Deyu; Zhang, Mou; Han, Wenhao; Wang, Yuan; Xu, Shudi; Tang, Kailin; Gao, Jian; Cao, Zhiwei (Frontiers in Chemistry, 2022)
Natural compounds (NCs) undergo complicated biotransformation in vivo to produce diverse forms of metabolites dynamically, many of which are of high medicinal value. Predicting the profiles of chemical products may help to narrow down possible candidates, yet current computational methods predicting biotransformation largely focus on synthetic compounds. Here, we proposed a method of MetNC, a tailor-made method for NC biotransformation prediction after exploring the overall patterns of NC in vivo metabolism. Based on 850 pairs of biotransformation dataset validated by comprehensive in vivo experiments with sourcing compounds from medicinal plants, MetNC was designed to produce a list of potential metabolites through simulating in vivo biotransformation, and then prioritize true metabolites into the top list according to the functional groups in compound structures and steric hindrance around the reaction sites. Compared with well-known peers of GLORYx and BioTransformer, MetNC gave the highest performance in both the metabolites coverage and the ability to short-list true products. More importantly, MetNC seemed to display extra advantage in recommending the microbiota-transformed metabolites, suggesting its potential usefulness in the overall metabolism estimation. In summary, complemented to those techniques focusing on synthetic compounds, MetNC may help to fill the gap of natural compounds metabolism and narrow down those products likely to be identified in vivo.